ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PENGAMBILAN KEPUTUSAN UNTUK MENGGUNAKAN JASA KLINIK PERAWATAN KULIT DI RTC SKIN CENTER KOTA KUPANG - Manafe, Charin Estefania; Fanggidae, Ronald P C; Nyoko, Antonio E L (Universitas Nusa Cendana, 2022)
Each line of business has a different strategy for managing and developing its business, including in skin care, which is predicted to grow in the coming years. Competition in the skincare business will benefit consumers because it will provide more profits. As a service company with potential and excellence in technology, RTC Skin Center has won the attention of the people of Kupang City. RTC Skin Center is a service business, that has expertise in the field of skin and genital care. The research approach used is descriptive quantitative with a number of samples was 100 respondents. The technique used in data collection is the survey method. Based on the results and discussion, this study concludes that there are 10 priority ratings as the main indicators to make the decision to use services at the RTC Skin Center. Keywords : Decision making, factor, Skincare